Use of customised pressure‐guided elastic bandages to improve efficacy of compression bandaging for venous ulcers. Issue 4 (9th August 2016) - Sermsathanasawadi, Nuttawut; Chatjaturapat, Choedpong; Pianchareonsin, Rattana; Puangpunngam, Nattawut; Wongwanit, Chumpol; Chinsakchai, Khamin; Ruangsetakit, Chanean; Mutirangura, Pramook
Abstract: Compression bandaging is a major treatment of chronic venous ulcers. Its efficacy depends on the applied pressure, which is dependent on the skill of the individual applying the bandage. To improve the quality of bandaging by reducing the variability in compression bandage interface pressures, we changed elastic bandages into a customised version by marking them with circular ink stamps, applied when the stretch achieves an interface pressure between 35 and 45 mmHg. Repeated applications by 20 residents of the customised bandage and non‐marked bandage to one smaller and one larger leg were evaluated by measuring the sub‐bandage pressure. The results demonstrated that the target pressure range is more often attained with the customised bandage compared with the non‐marked bandage. The customised bandage improved the efficacy of compression bandaging for venous ulcers, with optimal sub‐bandage pressure.